Correlation Of Left Ventricular Ejection Fraction And Spatial QRS-T Angle In Old Myocardial Infarct Patient - Karwiky, Giky; Achmad, Chaerul; Martanto, Erwan; Sanjaya, Ferdy (Jurnal Kardiologi Indonesia, 2021)
Objective: Spatial QRS-T angle (the angle between the QRS and T vectors) is a strong independent predictor of cardiovascular death. Spatial QRS-T angle calculations can be obtained from the ECG 12 lead with Kors visual transform applications closest to Frank lead system. Half of patients with coronary artery disease (CAD) died from sudden cardiac death (SCD) with Left Ventricular Ejection Fraction (LVEF) as a predictor. The aim of this study was to correlate spatial QRS-T with LVEF in patients with old myocardial infarction (OMI). Methods: This is a cross-sectional study in patients with OMI that have not undergone revascularization and have achieved medical therapy. 12-lead electrocardiography (ECG) and echocardiography were done simultaneously. Spatial QRS-T angle was measured by Kors visual transform applications. Statistical analysis was performed using Pearson correlation and multivariate analysis with linear regression. Results: 46 patients meet the inclusion criteria. Baseline characteristics: mean age 58 ± 8 years, 89% male, mean spatial QRS-T was 108.72 ± 43° with mean LVEF 39.39 ± 10%. The spatial QRS-T angle and LVEF was strong negative correlation (r=-0.66, p<0.01) after adjusted with left ventricular mass index (LVMI) correlation between spatial QRS-T angle and LVEF decreasing (r=-0.57, p<0.01). The Spatial QRS-T angle and LVEF of patients with OMI is negative correlation. Conclusion: The spatial QRS-T angle and LVEF of patients with OMI had negative correlation. Spatial QRS-T angle may be an easier index for assessing cardiac dysfunction in patients with OMI.